Good Corporate Governance Dalam Memprediksi Profitabilitas Perusahaan Pertambangan Yang Go Public Di Indonesia - Nurullaili Mauliddah; Tyasha Ayu Melynda Sari (Research Institution and Community Service Universitas Wijaya Kusuma Surabaya, 2022)
This study aims to analyze the conditions of GCG implementation in mining companies that go public in Indonesia and how it affects the profitability of companies proxied using Return on Equity (ROE). The independent variables in this study are GCG scores, managerial ownership, institutional ownership and DER. The data used is secondary data sourced from the Indonesia Stock Exchange in 2014-2019 with a sample of 10 mining companies that have passed as a sample through purposive sampling with several criteria. The results showed that GCG and managerial ownership had no significant effect on ROE, while institutional ownership and DER significantly adversely affected ROE. Exemplary GCG implementation and proper debt management will have an impact on increasing profitability.